2015
DOI: 10.1007/s11096-015-0235-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical care program for onco-hematologic outpatients: safety, efficiency and patient satisfaction

Abstract: The program has been implemented and evaluated successfully. It ensures a high quality and standard of pharmaceutical care with high patient satisfaction rate and the key points to prioritize for improvement in terms of safety (interactions and administration errors) and efficiency (adherence and permanence) of oral antineoplastic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
102
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(109 citation statements)
references
References 18 publications
2
102
2
3
Order By: Relevance
“…After reviewing the titles and abstracts, 617 records were excluded because they did not include a study of pharmacist interventions in adult patients with cancer; did not assess the impact of interventions; or included non‐ambulatory patients. The remaining 40 records were selected for full‐text examination, of which 11 met all the eligibility criteria and were included in this systematic review . The excluded studies and the reasons for their exclusion are detailed in Appendix 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After reviewing the titles and abstracts, 617 records were excluded because they did not include a study of pharmacist interventions in adult patients with cancer; did not assess the impact of interventions; or included non‐ambulatory patients. The remaining 40 records were selected for full‐text examination, of which 11 met all the eligibility criteria and were included in this systematic review . The excluded studies and the reasons for their exclusion are detailed in Appendix 2.…”
Section: Resultsmentioning
confidence: 99%
“…The assessment of the key components of pharmacist interventions showed that the studies were conducted at different outpatient settings, such as clinics, university hospitals and cancer centres or institutes. The main communication method with patients was face‐to‐face contact (72.7%) . The duration of the interventions ranged from 2 to 45 months, with most studies (n=5) reporting a follow‐up time of less than 12 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, a study including 249 oncology patients who were assisted through a CPCP with three clinical interviews over a 6‐month period demonstrated an increase in the percentage of patients with an adherence rate >90% in the intervention group compared with the control group (from 60.5% to 80.8%) ( P <.001). This programme reordered 275 medication errors and 362 pharmacist interventions, mainly to reinforce patient education …”
Section: Discussionmentioning
confidence: 99%